3x-3y=6

Subtract 3x from both sides of the equation.

-3y=6-3x

Divide each term by -3 and simplify.

Divide each term in -3y=6-3x by -3.

-3y-3=6-3+-3x-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=6-3+-3x-3

Divide y by 1.

y=6-3+-3x-3

y=6-3+-3x-3

Simplify each term.

Divide 6 by -3.

y=-2+-3x-3

Cancel the common factor of -3.

Cancel the common factor.

y=-2+-3x-3

Divide x by 1.

y=-2+x

y=-2+x

y=-2+x

y=-2+x

y=-2+x

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Reorder -2 and x.

y=x-2

y=x-2

Find the values of m and b using the form y=mx+b.

m=1

b=-2

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 1

y-intercept: -2

Slope: 1

y-intercept: -2

Choose 1 to substitute in for x to find the ordered pair.

Replace the variable x with 1 in the expression.

f(1)=(1)-2

Simplify the result.

Subtract 2 from 1.

f(1)=-1

The final answer is -1.

-1

-1

The y value at x=1 is -1.

y=-1

y=-1

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=(0)-2

Simplify the result.

Subtract 2 from 0.

f(0)=-2

The final answer is -2.

-2

-2

The y value at x=0 is -2.

y=-2

y=-2

Create a table of the x and y values.

xy0-21-1

xy0-21-1

Graph the line using the slope and the y-intercept, or the points.

Slope: 1

y-intercept: -2

xy0-21-1

Graph 3x-3y=6